Need for Communitarian Ethics in Mathematics Teaching-Learning in Engineering Careers - García-Ubaque, César-Augusto; Vergel, Rodolfo (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This article presents some reflections on ethics in mathematics classes in engineering majors. We conceptualize ethics as the forms of relationship with the other or the otherness forms. Once the production and learning of mathematics are conceived as processual events that occur in concrete human practice, ethics is considered an inescapable element to consider, as the theory of objectification suggests. In the first part, this study addresses a brief contextualization of the relationship between mathematics teaching and learning and engineering from an ethical point of view. Then, an approach to Radford's theory of objectification and its ethical position is presented. In the third part, this study addresses an instrument design that allowed to explore preliminarily in a group of university mathematics professors the types of ethics applied in the classrooms. The fourth part of the article focuses on the analysis of the responses. Finally, we present some reflections and suggestions for future studies.